Online remote ESL education challenges, opportunities and readiness among high school students during school closure - Lois Gwyn Peter; Adelina Asmawi (JOALL (Journal of Applied Linguistics and Literature), 2023)
The COVID-19 outbreak caused mass school closure, pushing teachers and students into online remote education and forcing them to adapt to unfamiliar pedagogical norms. Drawing on Koole’s (2009) Framework for the Rational Analysis of Mobile Education (FRAME) model, this study explored the challenges and opportunities of online remote ESL learning as experienced by four selected high school students from urban and rural Sarawak, Malaysia. It also explored the extent of their readiness for online remote ESL education one year into school closure. This study employed a multiple case study approach which included observations, document analysis and in-depth interviews of participants from multiple demographic categories. Findings discovered challenges that affected the students’ online remote ESL learning experience included the teacher’s physical absence, lack of engagement during lessons and unfavourable learning conditions. Online remote ESL learning also presented students with educational opportunities, particularly independent learning, online social learning and skills development. Findings suggested that urban students were ready, capable and equipped for online remote ESL learning whereas rural students were not as urban students had better digital resources, higher digital competency, sturdier support system, robust modes of instruction for online remote English lessons and higher language proficiency. This study concluded that individual characteristics of students, digital resources, language proficiency and appropriate learning environments play essential roles in supporting online remote ESL learning. Therefore, this study holds a significant theoretical implication for ESL education and the construct of Koole’s FRAME as it validates that when aspects related to the learner, device and social interactions in online remote learning are fulfilled, it can result in an ideal online remote learning experience.